Pedagogical Practices In Early Childhood Physical Education: A Systematic Literature Review Of Teaching Strategies, Curriculum, And Developmental Outcomes - Muhamamad Nurhisyam Ali Setiawan; Ardo Yulpiko Putra (JKP: Jurnal Khasanah Pendidikan, 2026)
Early childhood physical education is expected to develop movement competence while supporting cognitive, social-emotional, and lifelong participation outcomes, yet the pedagogical conditions that produce these benefits remain fragmented across teacher, curriculum, intervention, and assessment research. This systematic literature review synthesized recent evidence on teaching strategies, curriculum design, teacher competence, and developmental outcomes. A supplied Scopus export covering 2021 to 25 July 2026 was screened using a reproducible title-abstract-keyword filter and PRISMA 2020 reporting principles. Of 1,578 records, 316 met the topic filter, 56 were assessed for eligibility, and 44 empirical articles were included in a qualitative thematic synthesis. Four themes were identified: teacher capacity and professional learning (18 studies), curriculum design and implementation (12), instructional and play-based strategies (10), and assessment and quality assurance (4). Across themes, the strongest pattern was that structured but adaptable instruction, active and playful learning, adequate dosage, and sustained professional development were associated with improved fundamental movement skills, physical activity, fitness, self-regulation, enjoyment, and selected language or social-emotional outcomes. However, benefits depended on implementation fidelity, teacher confidence, contextual resources, and developmentally appropriate assessment. The review proposes an integrated practice model in which teacher learning, intentional curriculum, responsive pedagogy, and formative assessment operate as a coherent system rather than isolated components.